Failure analysis and structural behaviour of CFRP strengthened steel I-beams - Narmashiri, K.; Ramli Sulong, Nor Hafizah; Jumaat, Mohd Zamin (Elsevier, 2012)
This paper reports the experimental and numerical investigations on the Carbon Fibre Reinforced Polymer (CFRP) failure analysis and structural behaviour of the CFRP flexural strengthened steel l-beams. Understanding the CFRP failure modes is useful to find solutions for preventing or retarding the failures. One non-strengthened control beam and twelve strengthened beams using different types and dimensions of CFRP strips in both experimental test and simulation modelling studies were investigated. In the experimental test, four-point bending method with static gradual loading was applied. To simulate the specimens, the ANSYS software in full three dimensional (3D) modelling case and non-linear analysis method was utilized. The results show the CFRP failure modes used in flexural strengthening of steel l-beams include below point load splitting (BS), below point load debonding (BD), end delamination (EDL), and end debonding (ED). The occurrences and sequences of CFRP failure modes depended on the strengthening schedule. The structural performance of the CFRP strengthened steel beams also varied according to the strengthening specifications investigated in this research.